40 YEARS OF OUTER SPACE TREATY 1967 - Бєглий, О. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article highlights the historical significance of the Treaty on principles of the activities of States in the exploration and use of outer space, including the moon and other celestial bodies, adopted by resolution 2222 (XXI) of the UN General Assembly for establishing the rule of law in space.